Physical Exercise and 5-Hydroxytryptophan, a Precursor for Serotonin Synthesis, Reduce Penicillin-Induced Epileptiform Activity - Kayacan, Yildirim; Ghojebeigloo, Babak Elmi; Cerit, Gunay; Kocacan, Suleyman Emre; Ayyıldız, Mustafa (Academic Press Inc Elsevier Science, 2020)
Aim: Previous studies have shown that 5- hydroxytryptophan (5-HTP) and exercise play an important role in the synthesis of serotonin independently. The effects of the treadmill exercise and 5- hydroxytryptophan (5-HIP) on seizure mechanisms created by epileptiforrn activity with penicillin model were investigated in rats. Method: A total of 28 male albino Wistar rats were randomly divided into four groups: exercise (Ex), Control (Cnt), 5-hydroxytryptophan (5htp) and 5-hydroxytryptophan +/- exercise (5htpEx) groups. Treadmill exercise and gavage (25 mg/kg/day) were administered five days a week for ten weeks. Electrocorticogram data were recorded for 3 hat the end of the protocol using the Power-Lab data acquisition system. Spike frequency, amplitude, and latency time were analyzed offline. The significant differences among the groups were evaluated by one-way analysis of variance (ANOVA). Results: Spike frequency was observed at the highest level from the 20th minute in the Cnt group, and this continued until the end of the recording. The 5-HTP alone group did not affect epileptiform activity. At the 80th minute of penicillin injection, the epileptiform activity in the 5htpEx group decreased significantly compared with the Cnt, and this significance continued until the 110th minute. There was no statistical difference in the amplitude values of the groups. The 5htpEx group was significantly higher than both the Cnt and Ex group in the seizure latency times. Conclusions: It was determined that exercise reduced the spike number and delayed seizure significantly by potentiating the effect of 5-H1P. Given that 5-HTP used in combination with exercise can perform useful actions such as reducing seizure sensitivity and consequently improving the quality of life for individuals with epilepsy, it may be a potential candidate for the treatment of epilepsy in nonpharmacological methods. (C) 2020 Elsevier Inc. All rights reserved.
Ayyildiz, Mustafa/0000-0002-6594-3080; Ayyildiz, Mustafa/0000-0002-6594-3080; Çerit, Günay/0000-0001-9151-4071; Kayacan, Yildirim/0000-0003-2784-2980
Keywords: 5-Hydroxyuyptophan; Exercise; Epilepsy; Spike; Epileptiform Activity